The legality of police checkpoints in Nigeria - Obidimma, Emmanuel O. C. (African journal of law and criminology, 2015)
Police checkpoints are locations especially on the highway where police officers are stationed to check vehicle and drivers in consonance with their duty of prevention and detection of crime as well as the apprehension of offenders and preservation of law and order. But the proliferation of police checkpoints and the manner of operation of police officers at these checkpoints across the nation has called to question the legality of these checkpoints. This paper discusses the legality of police checkpoints in Nigeria with reference to the extant laws on the point and in comparison with the practice in civilized jurisdictions. The conclusion that is made is that notwithstanding the powers of the police to prevent and detect crime, police checkpoints, as presently conducted in Nigeria, are not only illegal, they also present a platform for the commission of more illegality. The paper recommends strict adherence to the law, respect of the citizens’ fundamental rights and adequate discipline of erring police officers as the way to curb this national embarrassment.